Pamphlets, Legislators and the Irish Economy: 1727-49: A Reconsideration. (1st December 2014) - Rees, Gordon
Abstract : A significant outcome of the revolution in the writing of Irish economic and social history in the 1960s and 1970s was the development among historians of a sceptical approach to contemporary pamphlets. With pamphleteers' comments on social and economic conditions no longer regarded as reliable, historians became reluctant to use the pamphlet literature. Now, almost half a century later, it is time to ask whether this scepticism has been carried too far. This article reassesses the value of contemporary pamphlets to the historian by analysing the political and economic pamphlets of the period between 1727 and 1749 in the context of other contemporary comment and practical political action. Using the correspondence of various leading political figures and the legislative record of the Irish parliament, the article seeks to evaluate the potential of the pamphlet literature as a guide to the preoccupations of the political elite and wider contemporary society. The article also re-examines the relationship between pamphlets and the political and economic realities, asking whether the pamphlet literature provides a better reflection of contemporary political and economic trends than has previously been acknowledged.